STUDI TENTANG LOYALITAS MEREK (KASUS PADA SHAMPO SUNSILK DI KOTA SEMARANG) - Santoso, Fitri Dhiastuti (Master of Management Diponegoro University, 2010)
Hair is the most valuable crown for women. For this reason, many shampoo producers competeone each other to provide the consumersâ€™ need and want to produce the good shampoo forthe consumer. Nevertheless, shampoo is classified to nondurable goods. Therefore, producersmust have a certain marketing to increase the brand preference in order to achieve theconsumersâ€™ brand loyalty. Sunsilk is a product of Unilever Indonesia, ltd. Unilever Indonesia, ltdcarry out some ways in marketing their product, such as advertise it on TV starred by famousartist, alter the package shape and size, add the shampoo variety, and logo alteration as well.Those efforts aim to increase the brand preference and then become a loyalty to Sunsilk.The research proposes 7 hypothesis, they are: brand focus advertisement influences the brandawareness (hypothesis 1), star attraction in advertisement influences the brand awareness(hypothesis 2), product design innovation influences the brand association (hypothesis 3),product package attraction influences the brand association (hypothesis 4), brand awarenessinfluences the brand preference (hypothesis 5), brand association influences the brand preference(hypothesis 6), brand preference influences the brand loyalty (hypothesis 7).The research sample is women in Semarang who use Sunsilk and ever watched Sunsilk advertisementâ€œAriel Peter Panâ€ version. There were 167 respondents. The analysis of data usedSEM (Structural Equation Model) from AMOS 16 software package. The proposed researchmodel is which is more than 2, 58 and the Determinant of Covariance Matrix value 81,741. Themeasurement of exogenous and endogen constructions tested using confirmatory analysisand proper full model test analyzed by using SEM where the value of Goodness of Fit Chisquare = 274, 835: probability = 0,55; GFI = 0, 874; AGFI = 0, 842; CFI = 0, 986; TLI = 0, 984;RMSEA = 0, 030; CMIN / DF = 1, 150. Based on the result, it can be concluded that theproposed model, is accepted. Therefore, Sunsilk brand loyalty can be reached by increasingbrand preference through brand awareness and brand association.